Pengaruh Fasilitas Infrastruktur Pendukung Keselamatan Dan Kenyamanan Pada Pengguna Jalan Di Bundaran Besar Kota Palangka Raya - Najwamuna Norazizah Rahmania; Dewantoro; Veronika Happy Puspasari (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
The Great Roundabout in Palangka Raya City is a significant symbol in Central Kalimantan Province, serving as a traffic intersection and a public space that supports social interaction. With the growing population and number of vehicles, various problems have emerged, such as congestion, accidents, and a lack of pedestrian comfort. This study aims to analyze the influence of infrastructure facilities on the safety and comfort of road users at the Great Roundabout. Using a literature review approach, this study identified 27 variables related to infrastructure, safety, and comfort. Factors affecting comfort are divided into two categories: internal factors, which include attitudes, awareness, and driving experience, and external factors, which include road conditions, the presence of other vehicles, and traffic management. The results of the analysis show that infrastructure, such as pedestrian bridges, wider sidewalks, and green open spaces, has a significant impact on improving the safety and comfort of road users. It is hoped that this study can provide deeper insights into the relationship between infrastructure facilities and road user experiences, and serve as a basis for the development of better policies in the planning and management of road infrastructure in urban areas, especially in Palangka Raya City.